Sosialisasi Pengurusan Nomor Induk Berusaha (NIB) Bagi Pelaku Usaha Mikro Kecil dan Menengah (UMKM) Perseorangan - Dian Puspita; Leni Anggraeni; Rina Wati; Widi Andewi (Communio: Jurnal Pengabdian Kepada Masyarakat, 2023)
Currently, the government is offering a lot of assistance, one of which is assistance and training to MSMEs regarding the impact of the Covid-19 pandemic. To get this facility, MSMEs must have a business license; one example is a Business Identification Number (NIB). This activity was conducted to answer problems and aims to introduce and increase understanding of making NIB and IUMK. The methods used are outreach, training and mentoring. Its implementation includes the delivery of theory and practice of making business legality. The result of the training was that participants' understanding of OSS, NIB and IUMK increased. Gumukmas is one of the villages in Pagelaran District, Pringsewu Regency, Lampung, which has hundreds of MSMEs registered with the Pringsewu Regency Cooperative and MSMEs Office. Realizing the importance of business licensing for MSME actors, the IBN Pringsewu service team conducted training to help residents, especially micro, small and medium enterprises, to recognize, know, and use the benefits of Business Identification Numbers for MSME actors. This activity aims to introduce what NIB and OSS are to business people in Gumukmas Village. This training focuses on making Business Identification Numbers through the OSS (Online Single Submission) Website; the practice mechanism includes data on MSME actors and data.